ChemInform Abstract: Zinc‐Mediated CH‐Activation of Tetrahydrofuran under Mild Conditions for the Regioselective Addition to Aryl‐Propiolates. Issue 48 (2nd December 2014) - Puenner, Florian; Hilt, Gerhard
Abstract Attempts upon initiation of the reaction by other alkyl bromides or other reducing agents fail.